The Potential of Wearable Systems Using Dielectric Elastomers (DE) - Chiba, Seiki; Waki, Mikio (Smart Wearable Technology, 2025)
Recent progress in dielectric elastomers has been remarkable. As an actuator, it is now possible to lift an 8 kg weight by more than 1 mm at a speed of 88 ms with a dielectric elastomer of only 0.15 g. As a sensor, it is capable of measuring from 0.01 N to 1,400 N with a very thin and small device, and can also use moisture sensors, stretch sensors, and tactile feedback. Therefore, by effectively combining these sensors, it is possible to create a wearable system with a fairly realistic sensation. In addition, dielectric elastomers are inexpensive, lightweight, have a simple structure, can be multi-layered, and are highly efficient. In the future, they are expected to be applied in various industrial machines. In this study, we analyzed the factors that improve the performance of dielectric elastomers and considered measures for industrialization. Based on this, various systems that can be applied to wearables have been considered. Received: 30 December 2024 | Revised: 12 February 2025 | Accepted: 3 March 2025 Conflicts of Interest The authors declare that they have no conflicts of interest to this work. Data Availability Statement Data sharing is not applicable to this article as no new data were created or analyzed in this study. Author Contribution Statement Seiki Chiba: Conceptualization, Methodology, Software, Validation, Formal analysis, Investigation, Resources, Data curation, Writing – original draft, Writing – review & editing, Visualization, Supervision, Project administration. Mikio Waki: Methodology, Software, Validation, Formal analysis, Investigation, Data curation, Writing – review & editing, Visualization.